Stability Analysis of Automatic Voltage Regulator with GA-PID Controller (مجلة العلوم الشاملة, 2025)
Excitation systems are crucial components in electric power generation systems, ensuring a stable terminal output voltage from synchronous generators. The AVR achieves this voltage stabilization by modulating the generator's exciter voltage. However, factors such as load variations and the generator's field windings induction can negatively impact the regulator's performance. This study investigates two distinct PID (Proportional-Integral-Derivative) controller tuning methods to achieve a stable, rapid, and efficient response to transient disturbances in terminal voltages. The first method involves designing a classical PID controller using the Ziegler-Nichols technique. The second approach utilizes genetic algorithms (GAs) to maximize the parameters of the PID controller. According to simulation data, the controller based on evolutionary algorithms considerably lowers error constants., rise time, and settling time compared to the Ziegler-Nichols method. Based on simulations performed in Matlab/Simulink, the PID coefficients optimized by the genetic algorithm provide superior closed-loop output. Furthermore, the controller GA-PID exhibits enhanced disturbance rejection and resilience to load variations when tracking set points and managing load disturbances.